(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Antimicrobial resistance (AMR) is a global health threat, which leads to increased morbidity, mortality, and healthcare expenses. Effective antimicrobial stewardship (AMS) is pivotal to control its spread. Nurses play a significant role in addressing AMR, but knowledge deficiency among undergraduate nursing students can hinder their preparedness for stewardship responsibilities. This study aims to determine the knowledge level of undergraduate nursing students about AMR. Methods: A cross-sectional study was conducted among 87 undergraduate nursing students, using a self-administered questionnaire. Data were analyzed using appropriate statistical methods. Descriptive statistics and chi-square tests were done. Results: None of the participants had a good level of knowledge on AMR. Majority (82.76%) of the participants were found to have poor knowledge regarding AMR and 17.24% of students had moderate knowledge. No significant association was found between awareness of AMS and Antibiotic Policy with level of knowledge of participants Conclusion: The study reveals significant gaps in undergraduate nursing students’ knowledge of AMR, highlighting the need for changes in curriculum and innovative educational strategies.